2016
DOI: 10.4236/health.2016.82020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aerobic Exercise Training on Basal Metabolism and Physical Fitness in Sedentary Women

Abstract: Objective: Aerobic exercises are the basic activity on fight against obesity. And obesity is related with metabolic rate. So our study is aimed to investigate the effects of 8 weeks aerobic exercise on basal metabolic rate and physical parameters. Methods: Sedentary women between the ages of 35-45 (n = 40) were randomized into control group (CG) (n = 20) and exercise group (EG) (n = 20). EG underwent 8 weeks of aerobic-run-walk exercise training: 3 days a week, 1 hour sessions. The CG was not trained. Basal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The studies conducted in this context are in parallel with the results of the current study. However, there are studies in the literature that show similarities with the results of the present study as well as studies that do not (13,21,29,1,18,12). Topyıldız (29) applied pilates exercise for 60 minutes 3 days a week for 4 weeks to 50 volunteer women aged 25-60 years who were overweight and found no statistical difference in body weight and lean body weight values, although increases were observed compared to pre-study values.…”
Section: Discussionsupporting
confidence: 86%
“…The studies conducted in this context are in parallel with the results of the current study. However, there are studies in the literature that show similarities with the results of the present study as well as studies that do not (13,21,29,1,18,12). Topyıldız (29) applied pilates exercise for 60 minutes 3 days a week for 4 weeks to 50 volunteer women aged 25-60 years who were overweight and found no statistical difference in body weight and lean body weight values, although increases were observed compared to pre-study values.…”
Section: Discussionsupporting
confidence: 86%
“…Exercise is done 4 times a week and lasts for 4 weeks. The frequency of this exercise is in accordance with the considerations (Fox, T.L.E.L., Bowers, R.W., dan Foss, 2013), (Kizilay et al, 2016).…”
Section: Methodssupporting
confidence: 85%
“…Furthermore, Kammoun et al (2022) observed a modest decrease in heart rate and a considerable improvement in heart rate variability (HRV) among middle-aged men participating in a 4-week walking football program. Additionally, Kizilay (2016) found that an 8-week run-walk training regimen led to a noteworthy and significant increase in basal metabolic rate (BMR) among sedentary women. Therefore, it is imperative to devise a comprehensive strategy that includes educational initiatives alongside walking football programs to achieve optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%